Operating conditions of a simulated moving bed chromatography unit for the purification of fructooligosaccharides - Nobre, Clarisse (2010)
C. Nobre acknowledges the F.C.T. - Fundacao para a Ciencia e a Tecnologia (Portugal) for the PhD Grant ref. SFRH/BD/32514/2006. A. Severino is funded by Belgian Fund for Scientific Research (F.S.R.- FNRS).This paper presents research results of the Belgian Network DYSCO (Dynamical Systems, Control, and Optimization), funded by the Interuniversity Attraction Poles Programme, initiated by the Belgian Federal Science Policy Office (BELSPO). The scientific responsibility rests with its authors.